2023
DOI: 10.1002/art.42427
|View full text |Cite
|
Sign up to set email alerts
|

Mediation of the Same Epigenetic and Transcriptional Effect by Independent Osteoarthritis Risk–Conferring Alleles on a Shared Target Gene, COLGALT2

Abstract: Objective. Over 100 DNA variants have been associated with osteoarthritis (OA), including rs1046934, located within a linkage disequilibrium block encompassing part of COLGALT2 and TSEN15. Here, we used human foetal cartilage, cartilage from arthroplasty patients, and a chondrocyte cell model to determine the target gene(s) at the locus and the mechanism of action. Methods. Genotyping and methylation array data of cartilage DNA (n=87) were used to determine if rs1046934 genotype associated with differential DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…We have reported that for several OA SNPs the association with CpG methylation observed in arthroplasty cartilage also occurs in foetal cartilage, implying that a proportion of OA genetic risk may be functionally active during skeletogenesis [ 33 , 34 ]. We therefore assessed whether the rs34195470 mQTL was detectable in foetal cartilage.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have reported that for several OA SNPs the association with CpG methylation observed in arthroplasty cartilage also occurs in foetal cartilage, implying that a proportion of OA genetic risk may be functionally active during skeletogenesis [ 33 , 34 ]. We therefore assessed whether the rs34195470 mQTL was detectable in foetal cartilage.…”
Section: Resultsmentioning
confidence: 99%
“…This implies that DNAm may be an intermediate between the genetic risk signal and changes in gene expression, with the causal variant altering methylation of the enhancer which then alters expression of the target gene. DNAm as a functional intermediate of genetic risk is a relatively common phenomenon [ 26 28 ] and we have previously used associating DNAm signatures to experimentally characterize OA risk loci and identify target genes of risk-conferring alleles [ 29 34 ]. These experiments have been conducted on cartilage from arthroplasty patients and on cartilage from human foetal samples, the latter used to assess whether OA risk alleles have functional impact during joint development [ 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…We have reported that for several OA SNPs the association with CpG methylation observed in arthroplasty cartilage also occurs in foetal cartilage, implying that a proportion of OA genetic risk may be functionally active during skeletogenesis [29,30]. We therefore assessed whether the rs34195470 mQTL was detectable in foetal cartilage.…”
Section: Replication Of the Mqtl And Aei Analysismentioning
confidence: 99%
“…This implies that DNAm may be an intermediate between the genetic risk signal and changes in gene expression, with the causal variant altering methylation of the enhancer which then alters expression of the target gene. DNAm as a functional intermediate of genetic risk is a relatively common phenomenon [22][23][24] and we have previously used associating DNAm signatures to experimentally characterize OA risk loci and identify target genes of risk-conferring alleles [25][26][27][28][29][30]. These experiments have been conducted on cartilage from arthroplasty patients and on cartilage from human foetal samples, the latter used to assess whether OA risk alleles have functional impact during joint development [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…The integration of DNAm data into genetic studies, such as the statistical fine mapping of GWAS signals, has identified the co-localisation of methylation quantitative trait loci (mQTLs) with genetic risk signals 8,[11][12][13] . This interplay between DNA sequence and CpG methylation status 14 has further been shown to underpin tissue-specific molecular mechanisms of gene expression within the joint 15,16 .…”
Section: Introductionmentioning
confidence: 96%